2014
DOI: 10.1590/1414-431x20143878
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and disorders of glucose metabolism: the role of glycosuria

Abstract: Hyperuricemia has been associated with hypertension, diabetes mellitus, and metabolic syndrome. We studied the association between hyperuricemia and glycemic status in a nonrandomized sample of primary care patients. This was a cross-sectional study of adults ≥20 years old who were members of a community-based health care program. Hyperuricemia was defined as a value >7.0 mg/dL for men and >6.0 mg/dL for women. The sample comprised 720 participants including controls (n=257) and patients who were hypertensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Our result was consistent with other previous investigations. 27,[31][32][33] It is noteworthy, this finding also reinforced the previous study that showed a pathogenesis overlap among hyperuricemia and metabolic syndrome. 2 In the diagnosis of hyperuricemia, especially at higher levels, clinical suspicion of coexistent metabolic syndrome should be required.…”
Section: Discussionsupporting
confidence: 88%
“…Our result was consistent with other previous investigations. 27,[31][32][33] It is noteworthy, this finding also reinforced the previous study that showed a pathogenesis overlap among hyperuricemia and metabolic syndrome. 2 In the diagnosis of hyperuricemia, especially at higher levels, clinical suspicion of coexistent metabolic syndrome should be required.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies stated that participants who were prediabetic or diabetic but without glycosuria had a similarly elevated prevalence of hyperuricemia. In contrast, diabetic patients with glycosuria had a null prevalence of hyperuricemia and excreted more UA and Sodium than diabetic subjects without glycosuria [26]. In our study, we found that UA levels significantly reduced in both sex in an unregulated diabetic group which are speculated by losing UA with glucose ( Table 4).…”
Section: Discussionmentioning
confidence: 39%
“…Consistently, in a recent prospective study including 10,802 Korean men, impaired fasting glucose (glucose 100–125 mg/dl) and diabetes mellitus were significantly associated with 13% and 53% lower risks of developing hyperuricemia, respectively, compared with those with normal fasting glucose levels after 6 years of followup . In contrast, a study showed that participants with pre–diabetes mellitus or diabetes mellitus but without glycosuria had an elevated prevalence of hyperuricemia . The findings can be explained by enhanced proximal tubule reabsorption in the early course of dysglycemia that decreases with the ensuing glycosuria at the late stage of the disorder .…”
Section: Discussionmentioning
confidence: 63%